Técnicas de extracción de compuestos de matrices vegetales - Mananita Otoya, Joel Homero (2022)
This review aims to provide up-to-date technical information on extraction mechanisms, their pros and cons, and factors influencing efficacy and also presents a comparative overview of the applications of the following modern extraction techniques (liquid extraction and hot water extraction), as an alternative to conventional extraction techniques for chemical and enzymatic extraction. The extraction and analysis of plant matrices is likely to play an important role in the overall effort to ensure the availability of high-quality plant-based products to consumers around the world. Sample preparation is of paramount importance to the development of analytical methods for the analysis of constituents present in botanicals and herbal preparations. In this research paper, the principle behind the operation of various extraction techniques, factors influencing method performance, extraction approaches are discussed. Emphasis is placed on techniques that are solvent and energetic.